Linking satisfaction to credit card decisions: an application of the Wallet Allocation Rule. Issue 2 (3rd April 2017) - Aksoy, Lerzan; Keiningham, Timothy L.; Buoye, Alexander; Ball, Joan
Abstract : Purpose: The purpose of this paper is to identify the key drivers of share of wallet for credit cards issued by either a credit union (CU) or bank using a Wallet Allocation Rule (WAR) framework. Design/methodology/approach: A survey approach engaging 1, 649 current CU members at nine CUs regarding their use of 3, 487 different credit cards is employed. Binary logistic regression is used to discriminate when CU issued vs bank issued credit cards are perceived to be "best" by their owners. Findings: This research indicates the key drivers differ significantly when CU members prefer a CU-issued credit card vs a bank-issued credit card. For example, CU-issued credit cards are attractive to some CU members because of prior relationships with the CU and offering lower interest rates on revolving balances. By contrast, customers who choose a bank-issued credit card are much more likely to be driven by the rewards offered on the card. Practical implications: Using the WAR key driver approach, managers can identify differentiating attributes that influence customers' perceptions of their rank vis-à-vis competition and thereby grow share. Originality/value: This research provides a significant contribution to both the banking literature and the scientific literature by examining the robustness of a relative metrics approach within the retail banking and CU market. It represents the first empirical analysis of a WAR key driver approach in the scientific literature.